Motivation Learning English During Pandemic - Adisty Aryani; Nazriani Lubis; Azhary Tambusai; Melly Lestari (Indonesian Journal of ELT and Applied Linguistics, 2021)
This study aims to determine the perception of EFL students towards learning English during the COVID-19 pandemic at SMKN 3 Medan. The data collection is done through interviews. There were 6 students of grade XI APL 4 participating in this study. Since this research has explored students’ perception and motivation derived from students’ experiences during distance studying carried out due to the covid-19 pandemic. Descriptive research using qualitative technique is considered the right approach. The results of this study are presented descriptively to reveal students’ perception and motivation comprehensively. The result found that E-Learning got a bad perception because it was flexible and ineffective.